Respuestas
Respuesta dada por:
8
Recuerda que la derivada de:
xⁿ = n*x^(n-1)
x = 1
a = 0, donde "a" es una constante
Entonces:
g(x) = 2x^5 - 7x⁴ + x³ - 3x² - x + 5
Derivando...
g'(x) = 5*2x⁴ - 4*7x³ +3x² - 2*3x - 1 + 0
g'(x) = 10x⁴ - 28x³ + 3x² - 6x - 1
¡Espero haberte ayudado, saludos!
xⁿ = n*x^(n-1)
x = 1
a = 0, donde "a" es una constante
Entonces:
g(x) = 2x^5 - 7x⁴ + x³ - 3x² - x + 5
Derivando...
g'(x) = 5*2x⁴ - 4*7x³ +3x² - 2*3x - 1 + 0
g'(x) = 10x⁴ - 28x³ + 3x² - 6x - 1
¡Espero haberte ayudado, saludos!
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años